Mapping Performance Assessment Tools of Practical Skills in Chemistry Education: Evidence from a Systematic Review - Faradhilla Bonita; Nahadi; Heli Siti Halimatul Munawaroh (Postgraduate, University of Mataram, 2026)
Performance assessment has emerged as an important approach in chemistry education to address the limitations of conventional testing. This study aims to systematically review the implementation of performance-based assessments in chemistry, focusing on instrument typology, educational context, and targeted competencies. Guided by the PRISMA protocol, a comprehensive search was conducted in the Scopus database for peer-reviewed research articles published between 2015 and 2025. Due to the very strict inclusion criteria that focused exclusively on validated chemistry-specific instruments, nine selected articles were synthesized. Results indicate that analytical rubrics remain the most dominant format (67% of reviewed tools), with digital video-based assessments emerging as a recent trend, while 88% of implementations are skewed towards higher education. These authentic tools consistently report positive impacts on students' practical competence and procedural engagement. However, pedagogical challenges remain: current instruments often fail to capture deep conceptual reasoning due to the high cognitive load experienced by students during active tasks. This review concludes that while performance assessments effectively measure technical compliance, global standardization of the Evidence-Centered Design (ECD) framework is urgently needed to address the current fragmentation of instruments and systematically align laboratory evidence with measurable conceptual milestones.